Transformasi Pendidikan Tinggi menuju Kemitraan sebagai Kekuatan yang Cukup untuk Memulai Mesin Dampak - Munib, Munib (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2019)
This study aims to describe: how the transformation of higher education to partnerships is a sufficient force to start an impact engine. This research is a qualitative literature study with the following functions: 1) assumptions; 2) the pervasive and supportive traditions. 3) Identification of gaps in previous research. Research design becomes a reflexive process at every stage of the research. Comparative analysis of the type of organization in terms of structure, culture, size, the like and characteristics observed to study the larger unit of analysis. Finally, social artifacts such as books, sculptures, pictures and buildings can be a unit of analysis. From the results of the discussion it can be concluded as follows: 1) Transformation of higher education understands the importance of knowledge of social and economic development, but the relevance of this idea questions the responsiveness of higher education (universities) to contemporary socio-economic problems which is still quite low. 2) Social change does not occur in one sector with a single driver at certain times. Change involves continuous efforts and synergies both within and across sectors, driving factors, and future philosophies. 3) Creating innovative ideas in existing organizations is very difficult. change from within is difficult, frustrating, and often unsuccessful. But the value is clear: Organizations have the resources, whether for education, lobbying, dissemination and replication, or defense against backlash.